Preferences for orthodontic treatment attributes among young adult malocclusion patients in Anhui, China: a discrete choice experiment - Fangyu Song; Dandan Yu; Shan Jiang; Yihui Li; Yuguang Liu; Wang Yao; Han Cheng; Jianguang Xu; Wenhua Xu; Lidan Wang; Yuanyuan Gu (BMC Oral Health, 2026)
Abstract Background Malocclusion is a common dental condition that affects both oral function and facial appearance, with substantial implications for psychological well-being and oral health-related quality of life. Despite continuing advances in orthodontic technology, evidence on patient preferences for the available treatment options remains limited. This study aimed to quantify preferences and willingness to pay (WTP) for key orthodontic treatment attributes among young adults with malocclusion in China. Methods A discrete choice experiment (DCE) was conducted in Anhui Province, China, with 349 young adults diagnosed with malocclusion. The experiment assessed preferences across four attributes: follow-up intervals, appliance comfort, aesthetics, and treatment cost. Data were analysed using a mixed logit model, and subgroup analyses were conducted to explore preference heterogeneity. WTP was estimated through simulation, and scenario analysis was used to estimate predicted uptake under alternative hypothetical pricing scenarios. Results Respondents showed strong preferences for treatments offering superior comfort (coefficient for ‘very good’: 2.255, P < 0.001) and aesthetics (coefficient for ‘very good’: 2.269, P < 0.001). Clear aligners had the highest predicted uptake in both hypothetical scenarios, including when priced higher than the other appliance profiles. The median WTP estimates were 18,110 Chinese Yuan (CNY) for improvement in comfort from poor to average and 18,633 CNY for improvement in aesthetics from poor to good. Exploratory subgroup analyses suggested that females placed greater weight on aesthetics, males on comfort, and lower-income respondents on cost. Scenario analysis indicated that reducing the price of clear aligners to the same level as ceramic brackets increased their predicted uptake from 56.4% to 81.8%. Conclusions Among young adults with malocclusion attending a tertiary stomatology hospital in Anhui Province, China, better comfort and aesthetics were strongly preferred, and clear aligners had the highest predicted uptake in the hypothetical scenarios. These findings highlight the importance of considering patient preferences when discussing orthodontic treatment options, while recognising that treatment cost and preference heterogeneity may influence patient choices.